Dry ramming material for intermediate frequency furnace and preparation method of dry ramming material
By using raw materials such as electromelting corundum and plate-shaped corundum, and introducing magnesium olive sand, magnesium chromium sand and zirconia, combined with resin and titanium dioxide, the problems of low sintering strength and insufficient corrosion resistance of dry ramming materials in medium-frequency furnaces are solved, achieving the effect of high-temperature volume stability and long-life use, while ensuring environmental protection.
Patent Information
- Application Number
- CN202411870631.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
The existing dry ramming materials for existing medium-frequency furnaces have low sintering strength, insufficient anti-shrink and corrosion resistance, and are prone to cracking, making it difficult to meet the needs of high-temperature volume stability and long-life use.
The raw materials such as electromelting corundum, plate-shaped corundum, magnesium olive sand, magnesium chromium sand and zirconia are used to introduce chromium oxide through magnesium chromium sand, and resin and titanium dioxide are added during the sintering process to improve the slag resistance and high-temperature volume stability of the ramming material.
It significantly improves the slag corrosion resistance and high-temperature volume stability of the dry ramming material, extends the service life, and avoids pollution problems caused by chromium oxide, achieving the goal of green and environmental protection.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of refractory materials for medium frequency furnaces, and particularly relates to a dry ramming mass for medium frequency furnaces and a preparation method thereof. Background Art
[0002] The medium frequency induction furnace (abbreviated as medium frequency furnace) has the characteristics of fast heating, intermittent operation, convenient operation, low pollution, high efficiency and energy saving, etc. It has a very wide range of applications and has become one of the important production equipment for carbon steel smelting, casting and alloy steel smelting. The refractory lining of the medium frequency furnace is an important component. Since the heating temperature of the medium frequency furnace can reach about 1600℃ or even higher, the lining material of the medium frequency furnace must not only have a sufficiently high refractoriness, but also ensure good high temperature volume stability, mechanical strength and slag erosion resistance at high temperatures. The service life of the lining material has a decisive influence on the production efficiency of the frequency furnace. In the prior art, dry ramming mass is often used as the material for preparing the lining of the medium frequency furnace. The dry ramming mass is composed of particles of different components and particle sizes, and is made into a lining with a certain density by strong ramming. During use, the working surface of the dry ramming material needs to be sintered to form a sintered layer with high strength to effectively resist the scouring and erosion of molten steel; the non-working surface should maintain an unsintered bulk structure to facilitate the absorption of thermal stress, so as to prevent the expansion of cracks in the working layer and absorb cracks.
[0003] At present, the traditional medium frequency furnace ramming mass generally uses corundum-magnesium oxide as the main raw material, which has the advantages of wear resistance, high temperature resistance and strong chemical stability. However, the existing corundum-magnesium ramming mass has a low sintering strength of the working layer during use, resulting in low anti-scouring and anti-erosion performance; in addition, the existing corundum-magnesium ramming mass has a large expansion coefficient and is prone to cracking when used intermittently. Therefore, how to improve the sintering strength of aluminum-magnesium dry ramming mass and improve its anti-erosion performance and high-temperature volume stability is the focus of developing high-performance dry ramming mass.
[0004] In order to improve the strength and corrosion resistance of dry ramming mass, Chinese patent CN104418601A discloses a medium frequency furnace ramming mass. By adding chromium oxide fine powder to the medium frequency furnace ramming mass, the ramming mass can be made denser, its strength can be enhanced, and its wear resistance and corrosion resistance can be improved. However, the chromium oxide introduced can cause serious pollution problems. Chinese patent CN109320217A discloses a corundum dry ramming mass for medium frequency induction furnace and its preparation method. The invention improves the anti-scouring performance, anti-corrosion performance and thermal shock resistance of the dry ramming mass by adding yttrium oxide fine powder, nickel oxide and ZrOCl2•8H2O fine powder. However, the introduced ZrOCl2•8H2O produces hydrogen chloride at high temperature, which has a strong irritating effect on the human body.
[0005] Therefore, it is of great significance to prepare a green and environmentally friendly dry ramming material with good high-temperature volume stability, strong corrosion resistance and anti-scouring ability. Summary of the invention
[0006] In view of the above deficiencies in the prior art, one of the objects of the present invention is to provide a dry ramming material for a medium frequency furnace, which is not only green and environmentally friendly, but also has good high-temperature volume stability and strong resistance to slag erosion.
[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0008] A dry ramming material for a medium frequency furnace comprises the following raw materials in parts by mass: 35-45 parts of fused corundum, 35-45 parts of plate-shaped corundum, 2-8 parts of forsterite sand, 2-8 parts of magnesia-chrome sand, 5-10 parts of zirconium oxide, 1-5 parts of resin, and 0.5-2 parts of titanium dioxide.
[0009] The dry ramming material for medium frequency furnace of the present invention uses corundum as the main raw material. Under the joint action of forsterite sand, magnesia-chrome sand and zirconium oxide, the slag erosion resistance and high temperature volume stability of the dry ramming material can be significantly improved. Among them, forsterite sand and corundum react to form magnesia-aluminum spinel, magnesia-chrome sand and corundum generate magnesia-aluminum spinel and aluminum-chrome spinel, and zirconium oxide and corundum react to form aluminum-zirconium spinel. Under the action of each spinel, the slag erosion resistance can be significantly improved. At the same time, these spinels have low thermal expansion coefficients and are not easy to crack under the condition of intermittent heating of the medium frequency furnace, thereby improving the service life of the lining furnace; in addition, forsterite sand and zirconium oxide can synergistically promote the reaction between forsterite sand and corundum, so that the dry ramming material has excellent slag erosion resistance and high temperature volume stability. Titanium dioxide can increase strength and density after sintering, and increase the formation speed of magnesium-aluminum, aluminum-chromium and aluminum-zirconium spinel; resin can improve the initial strength of the dry ramming material.
[0010] The present invention introduces chromium oxide through magnesia-chrome sand and changes the adding method of chromium oxide, thereby avoiding the occurrence of poisoning and being green and environmentally friendly.
[0011] Preferably, the dry ramming material comprises the following raw materials in parts by mass: 40 parts of fused corundum, 40 parts of plate-shaped corundum, 5 parts of forsterite sand, 5 parts of magnesia-chrome sand, 7 parts of zirconium oxide, 3 parts of resin, and 1 part of titanium dioxide.
[0012] Preferably, the particle size of the fused corundum is 0.075-5 mm, and the Al2O3 content in the fused corundum is greater than 99wt%.
[0013] Preferably, the particle size of the plate-like corundum is 0.045-1 mm; the Al2O3 content in the plate-like corundum is greater than 99.3 wt%.
[0014] Preferably, the particle size of the forsterite sand is less than 75 μm, the MgO content in the forsterite sand is 45wt%~65wt%, and the SiO2 content is 35wt%~55wt%.
[0015] Preferably, the particle size of the magnesia-chrome sand is less than 75 μm, the MgO content in the magnesia-chrome sand is 80wt%~90wt%, and the Cr2O3 content is 10wt%~20wt%.
[0016] Preferably, the particle size of the zirconium oxide is less than 2 μm, and the ZrO2 content in the zirconium oxide is greater than 99.9 wt%.
[0017] Preferably, the resin is a thermosetting phenolic resin.
[0018] Another object of the present invention is to provide a method for preparing the dry ramming mass for the medium frequency furnace, comprising the following steps: uniformly mixing 1 / 2 fused corundum, 1 / 2 plate-shaped corundum, forsterite sand, magnesia-chrome sand, zirconium oxide, resin, and titanium dioxide, and then adding the remaining 1 / 2 fused corundum and 1 / 2 plate-shaped corundum, and mixing them uniformly to obtain the dry ramming mass for the medium frequency furnace.
[0019] The present invention mixes part of the corundum and the fine powder uniformly first, and then adds the remaining corundum, so that the dry ramming material can be mixed more uniformly and the performance of the dry ramming material can be improved.
[0020] Compared with the prior art, the present invention is beneficial in that:
[0021] (1) The dry ramming mass for medium frequency furnace of the present invention uses corundum as the main raw material. Under the joint action of forsterite sand, magnesia chrome sand and zirconium oxide, the slag erosion resistance and high temperature volume stability of the dry ramming mass can be significantly improved.
[0022] (2) The present invention introduces chromium oxide through magnesia-chrome sand and changes the way of adding chromium oxide, thereby avoiding the occurrence of poisoning and being green and environmentally friendly. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The dry ramming material for a medium frequency furnace of the present invention comprises the following raw materials in parts by weight: 35-45 parts of fused corundum, 35-45 parts of plate-shaped corundum, 2-8 parts of forsterite sand, 2-8 parts of magnesia-chrome sand, 5-10 parts of zirconium oxide, 1-5 parts of resin and 0.5-2 parts of titanium dioxide.
[0025] In the following examples and comparative examples, the particle size of the fused corundum is 0.075-5 mm, and the Al2O3 content in the fused corundum is greater than 99 wt%.
[0026] The particle size of tabular corundum is 0.045~1mm; the Al2O3 content in tabular corundum is greater than 99.3wt%.
[0027] The particle size of forsterite sand is less than 75 μm, the MgO content in forsterite sand is 45wt%~65wt%, and the SiO2 content is 35wt%~55wt%.
[0028] The particle size of the magnesia-chrome sand is less than 75 μm, and the MgO content in the magnesia-chrome sand is 80wt%-90wt%, and the Cr2O3 content is 10wt%-20wt%.
[0029] The particle size of the zirconium oxide is less than 2 μm, and the ZrO2 content in the zirconium oxide is greater than 99.9 wt%.
[0030] The resin is a thermosetting phenolic resin.
[0031] Example 1
[0032] This embodiment provides a dry ramming material, comprising the following raw materials in parts by weight: 40 parts of fused corundum, 40 parts of plate corundum, 5 parts of forsterite sand, 5 parts of magnesia chrome sand, 7 parts of zirconium oxide, 3 parts of resin, and 1 part of titanium dioxide;
[0033] The preparation method of the dry ramming material of the present embodiment comprises the following steps:
[0034] S1. Weigh each component by weight;
[0035] S2. First, 20 parts of fused corundum, 20 parts of plate-shaped corundum, 5 parts of forsterite sand, 5 parts of magnesia chrome sand, 7 parts of zirconium oxide, 3 parts of resin and 1 part of titanium dioxide were mixed in a mixer for 25 minutes; then 20 parts of fused corundum and 20 parts of plate-shaped corundum were added, and the dry ramming material for the medium frequency furnace was obtained after mixing for 10 minutes.
[0036] During construction, the material is rammed and formed, the sintering temperature is 1680℃, the baking time is 10h, and the insulation time is 5h;
[0037] The physical and chemical properties of the ramming material are as follows: the bulk density after drying at 110℃ for 24h is 2.88g / cm 3 , flexural strength 0.3MPa;
[0038] 1100℃, 3h sintering volume density 2.83g / cm 3 , flexural strength 3.0MPa, linear change rate 0.7%;
[0039] 1600℃, 3h sintering volume density 2.62g / cm3 , flexural strength 6.0MPa, linear change rate 2.3%, slag erosion after 75 heats is 35mm.
[0040] The maximum operating temperature is 1705℃, the furnace age is 185 times, and the service life is long.
[0041] Example 2
[0042] This embodiment provides a dry ramming material, comprising the following raw materials in parts by weight: 35 parts of fused corundum, 47 parts of plate corundum, 7 parts of forsterite sand, 3 parts of magnesia chrome sand, 5 parts of zirconium oxide, 3 parts of resin, and 1.5 parts of titanium dioxide;
[0043] The preparation method of the dry ramming material of the present embodiment comprises the following steps:
[0044] S1. Weigh each component by weight;
[0045] S2. First, 15 parts of fused corundum, 15 parts of plate-shaped corundum, 7 parts of forsterite sand, 3 parts of magnesia chrome sand, 5 parts of zirconium oxide, 3 parts of resin and 1.5 parts of titanium dioxide were mixed in a mixer for 25 minutes; then 20 parts of fused corundum and 32 parts of plate-shaped corundum were added, and the mixture was mixed for 10 minutes to obtain a dry ramming material for a medium frequency furnace.
[0046] During construction, the material is rammed and formed, the sintering temperature is 1680℃, the baking time is 10h, and the insulation time is 5h;
[0047] The physical and chemical properties of the ramming material are as follows: 110℃, 24h drying volume density 2.85g / cm 3 , flexural strength 0.25MPa;
[0048] 1100℃, 3h sintering volume density 2.85g / cm 3 , flexural strength 2.9MPa, linear change rate 0.9%;
[0049] 1600℃, 3h sintering volume density 2.59g / cm 3 , flexural strength 5.3MPa, linear change rate 2.6%, slag erosion after 75 heats is 40mm.
[0050] The maximum operating temperature is 1700℃, the furnace age is 180 times, and the service life is long.
[0051] Example 3
[0052] This embodiment provides a dry ramming material, comprising the following raw materials in parts by weight: 40 parts of fused corundum, 37 parts of plate corundum, 3 parts of forsterite sand, 7 parts of magnesia chrome sand, 10 parts of zirconium oxide, 3 parts of resin, and 1 part of titanium dioxide;
[0053] The preparation method of the dry ramming material of the present embodiment comprises the following steps:
[0054] S1. Weigh each component by weight;
[0055] S2. First, 20 parts of fused corundum, 15 parts of plate-shaped corundum, 3 parts of forsterite sand, 7 parts of magnesia chrome sand, 10 parts of zirconium oxide, 3 parts of resin and 1 part of titanium dioxide were mixed in a mixer for 25 minutes; then 20 parts of fused corundum and 22 parts of plate-shaped corundum were added, and the mixture was mixed for 10 minutes to obtain a dry ramming material for a medium frequency furnace.
[0056] During construction, the material is rammed and formed, the sintering temperature is 1680℃, the baking time is 10h, and the insulation time is 5h;
[0057] The physical and chemical properties of the ramming material are as follows: 110℃, 24h drying volume density 2.80g / cm 3 , flexural strength 0.21MPa;
[0058] 1100℃, 3h sintering volume density 2.79g / cm 3 , flexural strength 2.8MPa, linear change rate 1.0%;
[0059] 1600℃, 3h sintering volume density 2.57g / cm 3 , flexural strength 5.2MPa, linear change rate 2.5%, slag erosion after 75 heats is 38mm.
[0060] The maximum operating temperature is 1700℃, the furnace age is 178 times, and the service life is long.
[0061] Comparative Example 1
[0062] The dry ramming material of this comparative example includes the following raw materials in parts by weight: 40 parts of fused corundum, 40 parts of plate-shaped corundum, 17 parts of magnesia, 3 parts of resin, and 1 part of titanium dioxide;
[0063] The preparation method of dry ramming mass comprises the following steps:
[0064] S1. Weigh each component by weight;
[0065] S2. First, 20 parts of fused corundum, 20 parts of plate-shaped corundum, 17 parts of magnesia, 3 parts of resin and 1 part of titanium dioxide were mixed in a mixer for 25 minutes; then 20 parts of fused corundum and 20 parts of plate-shaped corundum were added, and the dry ramming material for the medium frequency furnace was obtained after mixing for 10 minutes.
[0066] During construction, the material is rammed and formed, the sintering temperature is 1680℃, the baking time is 10h, and the insulation time is 5h;
[0067] The physical and chemical properties of the ramming material are as follows: 110℃, 24h drying volume density 2.87g / cm 3 , flexural strength 0.2MPa;
[0068] 1100℃, 3h sintering volume density 2.82g / cm 3 , flexural strength 2.6MPa, linear change rate 1.8%;
[0069] 1600℃, 3h sintering volume density 2.57g / cm 3 , flexural strength 4.5MPa, linear change rate 3.6%, slag erosion after 75 heats is 61mm.
[0070] The maximum operating temperature is 1705℃ and the furnace life is 75 heats.
[0071] Comparative Example 2
[0072] The dry ramming material of this comparative example includes the following raw materials in parts by weight: 40 parts of fused corundum, 40 parts of plate-shaped corundum, 10 parts of magnesia-chrome sand, 7 parts of zirconium oxide, 3 parts of resin, and 1 part of titanium dioxide;
[0073] The preparation method of the dry ramming material of the present embodiment comprises the following steps:
[0074] S1. Weigh each component by weight;
[0075] S2. First, 20 parts of fused corundum, 20 parts of plate-shaped corundum, 10 parts of magnesia-chrome sand, 7 parts of zirconium oxide, 3 parts of resin and 1 part of titanium dioxide were mixed in a mixer for 25 minutes; then 20 parts of fused corundum and 20 parts of plate-shaped corundum were added, and the mixture was mixed for 10 minutes to obtain a dry ramming material for a medium frequency furnace.
[0076] That is, compared with Example 1, the forsterite sand is omitted in this comparative example, and the weight portion of the magnesia-chrome sand is increased accordingly.
[0077] During construction, the material is rammed and formed, the sintering temperature is 1680℃, the baking time is 10h, and the insulation time is 5h;
[0078] The physical and chemical properties of the ramming material are as follows: 110℃, 24h drying volume density 2.84g / cm 3 , flexural strength 0.25MPa;
[0079] 1100℃, 3h sintering volume density 2.79g / cm 3 , flexural strength 2.7MPa, linear change rate 1.7%;
[0080] 1600℃, 3h sintering volume density 2.55g / cm 3 , flexural strength 4.8MPa, linear change rate 3.5%, slag erosion after 75 heats is 55mm.
[0081] The maximum operating temperature is 1705℃ and the furnace life is 85 heats.
[0082] Comparative Example 3
[0083] The dry ramming material of this comparative example includes the following raw materials in parts by weight: 40 parts of fused corundum, 40 parts of plate-shaped corundum, 5 parts of forsterite sand, 12 parts of magnesia-chrome sand, 3 parts of resin, and 1 part of titanium dioxide;
[0084] The preparation method of the dry ramming material of the present embodiment comprises the following steps:
[0085] S1. Weigh each component by weight;
[0086] S2. First, 20 parts of fused corundum, 20 parts of plate-shaped corundum, 5 parts of forsterite sand, 12 parts of magnesia chrome sand, 3 parts of resin and 1 part of titanium dioxide were mixed in a mixer for 25 minutes; then 20 parts of fused corundum and 20 parts of plate-shaped corundum were added, and the dry ramming material for the medium frequency furnace was obtained after mixing for 10 minutes.
[0087] That is, compared with Example 1, zirconium oxide is omitted in this comparative example, and the weight portion of magnesia-chrome sand is increased accordingly.
[0088] During construction, the material is rammed and formed, the sintering temperature is 1680℃, the baking time is 10h, and the insulation time is 5h;
[0089] The physical and chemical properties of the ramming material are as follows: 110℃, 24h drying volume density 2.82g / cm 3 , flexural strength 0.25MPa;
[0090] 1100℃, 3h sintering volume density 2.78g / cm 3 , flexural strength 2.8MPa, linear change rate 1.6%;
[0091] 1600℃, 3h sintered volume density 2.60g / cm 3 , flexural strength 4.9MPa, linear change rate 3.2%, slag erosion after 75 heats is 53mm.
[0092] The maximum operating temperature is 1705℃ and the furnace life is 90 heats.
[0093] The linear change rate, slag erosion and furnace age of the ramming materials of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.
[0094] Table 1 Linear change rate of ramming material, slag erosion and furnace age
[0095]
[0096] By comparing Examples 1 to 3 with Comparative Example 1, it can be found that, compared with conventional corundum-magnesia ramming materials, the dry ramming materials of the present invention have excellent slag erosion resistance and high temperature stability, and a long service life. By comparing Examples 1 with Comparative Examples 2 to 3, it can be found that forsterite and zirconium oxide can synergistically improve the slag erosion resistance and high temperature stability of the dry ramming materials.
[0097] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A dry ramming material for a medium frequency furnace, characterized in that: The dry ramming material comprises the following raw materials in parts by weight: 35-45 parts of fused corundum, 35-45 parts of plate-shaped corundum, 2-8 parts of forsterite sand, 2-8 parts of magnesia-chrome sand, 5-10 parts of zirconium oxide, 1-5 parts of resin, and 0.5-2 parts of titanium dioxide.
2. The dry ramming material for medium frequency furnace according to claim 1, characterized in that: The dry ramming material comprises the following raw materials in parts by weight: 40 parts of fused corundum, 40 parts of plate-shaped corundum, 5 parts of forsterite sand, 5 parts of magnesia-chrome sand, 7 parts of zirconium oxide, 3 parts of resin, and 1 part of titanium dioxide.
3. The dry ramming material for medium frequency furnace according to claim 1, characterized in that: The particle size of the fused corundum is 0.075-5 mm, and the Al2O3 content in the fused corundum is greater than 99wt%.
4. The dry ramming material for a medium frequency furnace according to claim 1, characterized in that: The particle size of the plate-shaped corundum is 0.045-1 mm; the Al2O3 content in the plate-shaped corundum is greater than 99.3wt%.
5. The dry ramming material for medium frequency furnace according to claim 1, characterized in that: The particle size of the forsterite sand is less than 75 μm, the MgO content in the forsterite sand is 45wt%~65wt%, and the SiO2 content is 35wt%~55wt%.
6. The dry ramming material for medium frequency furnace according to claim 1, characterized in that: The particle size of the magnesia-chrome sand is less than 75 μm, the MgO content in the magnesia-chrome sand is 80 wt % to 90 wt %, and the Cr2O3 content is 10 wt % to 20 wt %.
7. The dry ramming material for medium frequency furnace according to claim 1, characterized in that: The particle size of the zirconium oxide is less than 2 μm, and the ZrO2 content in the zirconium oxide is greater than 99.9 wt%.
8. The dry ramming material for medium frequency furnace according to claim 1, characterized in that: The resin is a thermosetting phenolic resin.
9. The method for preparing a dry ramming material for a medium frequency furnace according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1 / 2 fused corundum, 1 / 2 plate-shaped corundum, forsterite sand, magnesia chrome sand, zirconium oxide, resin and titanium dioxide are mixed evenly, and then the remaining 1 / 2 fused corundum and 1 / 2 plate-shaped corundum are added and mixed evenly to obtain the dry ramming material for the medium frequency furnace.
Citation Information
Patent Citations
Medium-frequency furnace ramming material
CN104418601A
Corundum dry type ramming material for medium-frequency induction furnace and preparation method of corundum dry type ramming material
CN109320217A